(untitled) (Bioscience Journal, 2021)
Cover crops promote nutrient cycling, and lime and gypsum can alter the soil physical attributes. This study aimed to evaluate the effect of lime and gypsum rates applied to a no-tillage system with addition of residues of three cover crops on the soil physical attributes. This experiment was carried out in chapadão do sul-ms. The treatments were comprised of three cover crops (Urochloa ruziziensis, fallow, and Pennisetum glaucum), with gypsum (0, 2.3 and 4.6 Mg ha-1) and lime applied at a dose of 0, 2, 4, 6 Mg ha-1).The attributes evaluated were: soil density, macroporosity, microporosity, total porosity and penetration resistance. The soil of the experiment was classified an Oxisol. Cover crops and lime and gypsum improved macroporosity, microporosity and total porosity at all depths, 0-0.2 m. Millet presented lower values for penetration resistance with the lime application and without gypsum application. No residual effect on soil density was detected for lime and gypsum application or cover crops in the 0.1-0.2 m layer. Brazilian Cerrado producers will have a well-defined management system to follow aiming at improving the soil physical attributes.